Conceptual Metaphors in The Album Folklore By Taylor Swift - Masyithah Daniyah Rahmah; Ni Luh Ketut Mas Indrawati; I Nyoman Aryawibawa (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The undergraduate thesis entitled “Conceptual Metaphors in the Album Folklore by Taylor Swift” aims to analyze the conceptual metaphors in the Folklore album and analyze what are the meanings of the conceptual metaphors found. Metaphors are widely used in human life to create easier understanding of the form of communication. Metaphors are not merely ornamentals but they also take the roles of fundamental cognitive tools that develop how human beings understand and explore the world. This study was conducted by using a qualitative method. The Album Folklore was used as the data source. The data were collected using documentation technique analyzed through a descriptive-qualitative approach. The theory used for this study was Conceptual Metaphor Theory by George Lakoff and Mark Johnson. The findings show that there are three types of conceptual metaphor in the album. Firstly, five structural metaphors were found in the album specifically in the songs namely “The Last Great American Dynasty”, “Mirrorball”, “This Is Me Trying”, “Illicit Affair”, and “Betty”. Secondly, five orientational metaphors were found in the album, specifically in the songs namely “Cardigan”, “The Last Great American Dynasty”, “Exile ft. Bon Iver”, and “Epiphany”. Thirdly, five ontological metaphors were found in the album specifically in the songs namely “Cardigan”, “The Last Great American Dynasty”, “Exile. Ft. Bon Iver”, “Mirrorball”, and “Invisible String”.